19th International Symposium in Robot and Human Interactive Communication 2010
DOI: 10.1109/roman.2010.5598641
|View full text |Cite
|
Sign up to set email alerts
|

Tactile interaction with a humanoid robot for children with autism: A case study analysis involving user requirements and results of an initial implementation

Abstract: Abstract-The work presented in this paper is part of our investigation in the ROBOSKIN project. The project aims to develop and demonstrate a range of new robot capabilities based on the tactile feedback provided by a robotic skin. One of the project's objectives is to improve human-robot interaction capabilities in the application domain of robot-assisted play. This paper presents design challenges in augmenting a humanoid robot with tactile sensors specifically for interaction with children with autism. It r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Precursor studies which were carried out by the authors to elicit high level requirements for skin based interaction for these children were reported in [36]. This was followed by a series of preliminary experimental investigations with initial play scenarios that were conducted with children with autism and the robot KAS-PAR, providing essential observational data on children's behaviour during child-robot tactile interaction which were reported in [37,38]. These precursor studies provided valuable input to the development of the tactile play scenarios reported here.…”
Section: The Play Scenariosmentioning
confidence: 99%
“…Precursor studies which were carried out by the authors to elicit high level requirements for skin based interaction for these children were reported in [36]. This was followed by a series of preliminary experimental investigations with initial play scenarios that were conducted with children with autism and the robot KAS-PAR, providing essential observational data on children's behaviour during child-robot tactile interaction which were reported in [37,38]. These precursor studies provided valuable input to the development of the tactile play scenarios reported here.…”
Section: The Play Scenariosmentioning
confidence: 99%
“…Secondly, the abovementioned earlier studies examined how children with autism interacted and played in open-ended, exploratory settings with robots. According to Parten's research on play [40], we can classify some of the forms of play in these studies as parallel (two children with autism play in their own ways with the same robot at the same time, either without acknowledging each other or by acknowledgment without communication [48,65]), some as associative (a child with autism imitates a robot and communicates with its human adult controller [29,[46][47][48][49]), and on a few occasions, cooperative (two high-functioning children with autism spontaneously interact and communicate to organize a game together with a reactive robot [65], or a child with autism plays a two-player game with an experimenter while interacting minimally with them [29]). In these studies as well as others, there have been few cases of the children participating in cooperative play.…”
Section: Novel Pilot Studymentioning
confidence: 99%
“…One such behavior is social touch, with which people with autism are generally uncomfortable [53]. Using a relatively non-threatening social robot has been proposed as a way to teach children with autism about social touch, in order to make them more comfortable with touch [423]. In two explorative studies, children with autism were allowed to interact freely with a child-like robot that had touch sensors embedded in its skin [422,423].…”
Section: Touch By Robots In Healthcarementioning
confidence: 99%
“…Using a relatively non-threatening social robot has been proposed as a way to teach children with autism about social touch, in order to make them more comfortable with touch [423]. In two explorative studies, children with autism were allowed to interact freely with a child-like robot that had touch sensors embedded in its skin [422,423]. The children were observed to touch the robot on different body locations, such as its hands, wrists, and face, and the children were found to use different types of touch, including grasping, poking, and stroking [422,423].…”
Section: Touch By Robots In Healthcarementioning
confidence: 99%
See 1 more Smart Citation